2018
DOI: 10.1002/ijgo.12600
|View full text |Cite
|
Sign up to set email alerts
|

FIGO postpartum intrauterine device initiative: Complication rates across six countries

Abstract: PPIUD has low complication rates and can be safely inserted by a variety of trained health staff. Given the immediate benefit of the one-stop approach, governments should urgently consider adopting this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
5
20

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 12 publications
4
69
5
20
Order By: Relevance
“…These were vital in establishing PPIUD as a useful method of postpartum contraception in the six countries. These outcomes are discussed in another article in this Supplement by Makins et al . We also instituted an audit of structure and process at regular intervals using fixed proformas to ensure that the institutions met all the requirements to carry out high‐quality counselling and insertion services.…”
Section: Resultsmentioning
confidence: 99%
“…These were vital in establishing PPIUD as a useful method of postpartum contraception in the six countries. These outcomes are discussed in another article in this Supplement by Makins et al . We also instituted an audit of structure and process at regular intervals using fixed proformas to ensure that the institutions met all the requirements to carry out high‐quality counselling and insertion services.…”
Section: Resultsmentioning
confidence: 99%
“…Estos datos fueron vitales para llegar a la conclusión de que el DIUPP era un método anticonceptivo posparto útil en los seis países participantes. Makins et al 19 analizan estos resultados en otro artículo de este suplemento. También realizamos auditorías periódicas de la estructura y el procedimiento utilizando formularios fijos para asegurarnos de que los centros cumplían todos los requisitos necesarios para ofrecer un servicio de asesoramiento e inserción de alta calidad.…”
Section: │ Dificultadesunclassified
“…In total, 36 766 women had PPIUD inserted across the six countries and follow-up of just over 50% demonstrated that expulsion rates were lower than previously reported at 2.6%. 10 Rates of severe infection (pelvic inflammatory disease) were as low as 0.01% and there was not one single case of perforation. The methodology taught and used was high insertion at the uterine fundus using the Kelly forceps.…”
mentioning
confidence: 98%
“…On‐the‐job training was developed in Nepal and was found to be highly successful, with the benefit of not taking health personnel away from the work place for organized training . Task sharing of insertion of IUDs by midwives and nurses in India, Nepal, Kenya, and Tanzania proved to be extremely successful, with escalation of acceptance rates and very little variance in complication rates. Training of lay people as counsellors in Bangladesh had some advantages albeit not the anticipated impact on PPIUD acceptance, which reflected the multifaceted factors that are at play in some cultures where the woman is not the decision maker when it comes to her own sexual and reproductive health.…”
mentioning
confidence: 99%